Faktor-Faktor yang Berpengaruh Terhadap Kejadian Ventilator Associated Pneumonia - Nadya Salsabilah; Ari Wahyuni; Liana Sidharti (Medula, 2023)
Nosocomial infections also reffered to as healthcare-asscociated infections (HAI). This infection can occur both while in the treatment room, during surgical procedurs or actions, and it can also be transmitted through medical devices that have contact with patients such as mechanical ventilators. The use of a mechanical ventilator machine is intended as a life saving measure in critical patients and is usually found in the intensive care unit (ICU) room of a hospital. Ventilator associated pneumonia is a risk that can occur when using a mechanical ventilator machine. VAP is nosocomial pneumonia in patients who have mechanically ventilated with endotracheal tube and tracheostomy for at least 48 hours. In United States, Ventilator Associated Pneumonia is one of the causes of mortality in patients with a mortality rate of 13%. In Europe, mortality rate due to early Ventilator Associated Pneumonia is 19,2% and late Ventilator Associated Pneumonia is 31,4%. Ventilator associated pneumonia is reported to have varying incidence rates ranging from 9-27%. The mortality rate from ventilator associated pneumonia can be more than 50%. This event is influenced by several risk factors, one of which is the duration of using a mechanical ventilator. The use of a mechanical ventilator, especially during the installation of an endotracheal tube (ETT) can damage the defense barrier in the airways, the installation of an ETT can also damage the mucociliary and tracheal epithelium and interfere with the cough reflex. This allows pathogens to invade the lower respiratory tract resulting in ventilator associated pneumonia.